Development of network slicing mechanisms for OpenSlice - Santos, Eduardo Henrique Ferreira (2024)
The rapid advancement of telecommunications networks, such as 5G and beyond, has paved the way for transformative technologies and innovative services. Operators have begun to use virtualization techniques to maintain their technologies, moving away from dedicated networking hardware. Virtualization techniques and paradigms, such as Network Functions Virtualization (NFV), can significantly reduce costs while expanding the range of scenarios supported without changing the infrastructure. On the other hand, Verticals are becoming more interested in the performance improvements that come with 5G technologies. To meet the diverse needs of various industries and applications, traditional approaches to network management and service provisioning encounter significant challenges. Network slicing has emerged as a promising solution to address these challenges, as it enables the partitioning of a physical network into virtual slices, each customized to specific use cases and applications. To fully leverage the benefits of Network Slicing, one may integrate Network Slicing mechanisms into an Operations Support System (OSS), such as OpenSlice, an OSS currently under the umbrella of ETSI. This dissertation aims to integrate network slicing mechanisms into OpenSlice, enabling network slice lifecycle management operations. To achieve this objective, certain current features of OpenSlice need improvement while new ones need to be implemented. These contributions will involve enhancing various aspects and components of the platform to provide it with network-slicing mechanisms.